An urban full secondary school environmental and design studies / Josmin Yahya - Yahya, Josmin; Norrdin, Khairiah; Salim, Rahmat; M Yusof, Samsudin (Faculty of Architecture, Planning and Surveying, 1978)
The study on which the Report is based was limited in several ways. Time was short and any studies to be done on any school would take a long processing period in the Ministry of Education before any permission was granted. Our experiences were only tool to the understanding of the academic and behavioral patterns on school. Any views forwarded do not imply the expression of any opinion on the part of the team concerning the legal status of the Authority, or concerning the delimitation of the frontiers of the Authority, Opinions expressed in the report are not to underestimate the present condition, but to look through and study the possibilities for better conditions.